Firm-Specific Determinants Variable of Insurers’ Insolvency in Zimbabwe - Aluko, Timothy Olaniyi; Makumbe, Kudakwashe Carol (Acta Universitatis Danubius. Œconomica, 2024)
Insurance companies safeguard the resources necessary for various other economic sectors to enhance economic growth and foster favourable investment opportunities. This study examines the determinants of insolvency for non-life insurers in Zimbabwe. This was achieved by examining the impact of firm-specific variables on solvency. A panel of secondary data from 2017 to 2022 selects seventeen non-life insurance businesses from Zimbabwe. Insurance and Pension Commission (IPEC) reports provide the financial statements for these non-life insurance companies. The research examines two explanatory factors: investment performance and return on assets (profitability). The Statistical Package for Social Science (SPSS) regression model guides the investigation into the relationship between these factors and solvency. This study employs the solvency ratio as a proxy for solvency. The study’s results indicate that a firm’s size and claims ratio have a positive impact on the investment performance and profitability of non-life insurers experiencing insolvency. To manage investment portfolios properly, the paper recommends short-term insurers hire qualified and experienced investment analysts. To encourage insurance companies to honour claims and maintain their financial stability even when losses increase, the regulator must publish a risk-based capital structure and prioritise the implementation of policies and regulations that support sound financial management practices among non-life insurance companies.